Functional properties of equine adipose-derived mesenchymal stromal cells cultured with equine platelet lysate - Hagen, Alina; Niebert, Sabine; Brandt, Vivian-Pascal; Holland, Heidrun; Melzer, Michaela; Wehrend, Axel; Burk, Janina (Frontiers in Veterinary Science, 2022)
Successful translation of multipotent mesenchymal stromal cell (MSC)-based therapies into clinical reality relies on adequate cell production procedures. These should be available not only for human MSC, but also for MSC from animal species relevant to preclinical research and veterinary medicine. The cell culture medium supplementation is one of the critical aspects in MSC production. Therefore, we previously established a scalable protocol for the production of buffy-coat-based equine platelet lysate (ePL). This ePL proved to be a suitable alternative to fetal bovine serum (FBS) for equine MSC culture so far, as it supported MSC proliferation and basic characteristics. The aim of the current study was to further analyze the functional properties of equine MSC cultured with the same ePL, focusing on cell fitness, genetic stability and pro-angiogenic potency. All experiments were performed with MSC from n = 5 horses, which were cultured either in medium supplemented with 10% FBS, 10% ePL or 2.5% ePL. MSC cultured with 2.5% ePL, which previously showed decreased proliferation potential, displayed higher apoptosis but lower senescence levels as compared to 10% ePL medium (p < 0.05). Demonstrating their higher genetic stability, non-clonal chromosomal aberrations, such as polyploidy, occurred less in MSC cultured with 10% ePL. Clonal aberrations in the MSC were neither observed in FBS nor in 10% ePL medium. Analysis of MSC and endothelial cells in an indirect co-culture revealed that the ePL supported the pro-angiogenic effects of MSC. In the 10% ePL group, more vascular endothelial growth factor (VEGF-A) was released and highest VEGF-A concentrations were reached in the presence of ePL and co-cultured cells (p < 0.05). Correspondingly, MSC expressed the VEGF receptor-2 at higher levels in the presence of ePL (p < 0.05). Finally, MSC and 10% ePL together promoted the growth of endothelial cells and induced the formation of vessel-like structures in two of the samples. These data further substantiate that buffy-coat-based ePL is a valuable supplement for equine MSC culture media. The ePL does not only support stable MSC characteristics as demonstrated before, but it also enhances MSC functional properties.